29. CLINICAL CHARACTERISTICS AND ENDOSCOPIC IMAGES IN CHILDREN WITH PEPTIC ULCER AT NGHE AN OBSTETRICS AND PEDIATRICS HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Peptic ulcers in children are less common than in adults, however, they tend to be increasingly younger, mainly chronic due to Helicobacter pylori infection (HP). Objective: Describe clinical characteristics and endoscopic images in children with peptic ulcers at Nghe An Obstetrics and Pediatrics Hospital. Research subjects and methods: A cross-sectional descriptive study on 778 children with peptic ulcers infected with HP at Nghe An Obstetrics and Pediatrics Hospital. Results: Abdominal pain is the most common clinical symptom with 92,0%. Gastroduodenal endoscopy images show that gastritis accounts for a high rate of 93,6% and 6,4% of duodenal ulcers. Lesions were mainly found at the gastric antrum, accounting for 83,8%, and duodenal ulcers from 1 ulcer or more, accounting for 82,0%. Clinical symptoms of the disease are often non-specific in children, so combining clinical examination and gastrointestinal endoscopy is very valuable in diagnosing and directing the treatment of peptic ulcers in children. Conclusion: The age of gastric and duodenal ulcers in children is from 6 to 12 years old, the incidence rate of male children is 1.5 times higher than that of female children. Abdominal pain symptoms are the most common clinical symptoms with 92.0%. Gastritis lesions account for a high rate of 93.6% and 6.4%, the lesions are often located in the antrum and duodenum through gastroduodenal endoscopy.
Keywords: Peptic ulcers, children, gastrointestinal endoscopy, Helicobacter pylori.